Generic skills needs for graduate employment in the aquaculture, fisheries and related sectors in Europe - Pita, Cristina (2016)
There is an increasing demand for highly skilled workers in all advanced industrialised economies. Although most jobs require occupation-specific skills to carry them out, it is widely recognised that generic skills are ever more needed by job seekers, to increase job opportunities and maintain employability; this applies to all sectors of the economy, from selling cars to undertaking marine research. Several recent European Union strategy documents emphasise the importance of generic skills. However, the apparent mismatch between the skills sets that employers seek and that job seekers offer remains a major challenge. This paper focuses on perceptions of and attitudes to generic skills training for university graduates intending to gain employment in aquaculture, fisheries or other marine sectors and presents the results of a survey administered to academics, industry representatives, students (at different stages of their academic career) and graduates. The various respondents regarded most of the 39 generic skills under investigation as important, with none classified as unimportant. However, students undertaking different types of degree (i.e. B.Sc., M.Sc. and Ph.D.) prioritized different generic skills and the level of importance ascribed to generic skills training increased as students progressed in their university careers. On the other hand, university staff and other employers were fairly consistent in their choice of the most important generic skills. We argue that there remains a need to place generic skills and employability attributes and attitudes at the centre of the higher education curriculum.